Terrari - CLCM Architects (2004)
Proyecto de renovación urbana en Barcelona con motivo del <Fórum>
Keywords: LAY, CHARMAINE; MURO, CARLES; AZULAY, JUAN; PAEZ, ROGER; ESPAÑA; CATALUNYA; BARCELONA; JARDINES ZOOLOGICOS; ACUARIOS; PROYECTOS